Analyzing isolated degeneration of lumbar facet joints: implications for degenerative instability and lumbar biomechanics using finite element analysis - Park, Jun Sung; Goh, Tae Sik; Lee, Jung Sub; Lee, Chiseung (Frontiers in Bioengineering and Biotechnology, 2024)
This study aimed to investigate the impact of facet joint degeneration on the degenerative changes and diseases of the lumbar spine. A finite element model of the lumbar spine (L1–S1) was fabricated and validated to study the biomechanical characteristics of the facet joints. To simulate degeneration of the facet joint, the model was divided into four grades based on the number of degenerative segments (L4–L5 or L4–S1) and the contact condition between the facet joint surfaces. Finite element analysis was performed on four spine motions: flexion, extension, lateral bending, and axial torsion, by applying a pure moment to the upper surface of L1. Important parameters that could be used to confirm the effect of facet joint degeneration on the lumbar spine were calculated, including the range of motion (ROM) of the lumbar segments, maximum von Mises stress on the intervertebral discs, and reaction force at the facet joint. When analyzed by dividing it into degenerative onset and onset-adjacent segments, lumbar ROM and the maximum von Mises stress of the intervertebral discs decreased as the degree of degeneration increased in the degenerative onset segments. The reaction force at the facet joint decreased with flexion and increased with lateral bending and axial torsion. In contrast, lumbar ROM of the onset-adjacent segments remained almost unchanged despite severe degeneration of the facet joint, and the maximum von Mises stress of the intervertebral discs increased with flexion and extension but decreased with lateral bending and axial torsion. Additionally, the facet joint reaction force increased with extension, lateral bending, and axial rotation. This analysis, which combined the ROM of the lumbar segment, maximum von Mises stress on the intervertebral disc, and facet joint reaction force, confirmed the biomechanical changes in the lumbar spine due to the degeneration of isolated facet joints under the load of spinal motion. In the degenerative onset segment, spinal instability decreased, whereas in the onset-adjacent segment, a greater load was applied than in the intact state.